The Three-Dimensional Approach of Total Quality Management, an Essential Strategic Option for Business Excellence - Armenia Androniceanu (Amfiteatru Economic)
In a complex and dynamic business environment, managers widely appeal to modern methods and techniques that would help them cope with the competition and offer their customers new, attractive, good quality products and services and at competitive prices. In this context, total quality management is a viable and sustainable option that can systematically contribute to the consolidation of the capacity of organizations. The aim of this paper was to put forth a three-dimensional approach of total quality management and provide some concrete action ways through which organizations in Romania that implement total or partial quality management integrated systems would produce significant competitive advantages. The main research methods used were: the questionnaire, document analysis, applications offered by Word and Excel and the Statistical Package for Social Sciences, one of the most complete software packages with which we calculated means and standard deviations and determined and analysed correlations between variables and various quality parameters. In this research, have been identified the main key success factors, the vulnerabilities and weaknesses of the systems, their causes and the necessary changes through which the threedimensional approach of total quality management could become a preferred strategic option with a major positive impact upon business excellence. The most important results obtained are a three-dimensional approach of the Total Quality Management and a substantial number of certain proposals for the Romanian firms in order to achieve business excellence.